Mencari Jejak-jejak Autograf Perjanjian Lama di dalam Septuaginta - Brando V. Kondoj (Veritas : Jurnal Teologi dan Pelayanan, 2017)
For too long the Septuagint, the first translation of the Hebrew Old Testament, has been sidelined and not given a credible hearing in seeking to discern the text of the original autographs of the Old Testament which have been lost in antiquity. Even though that has been the case, the new direction in recent textual studies, which has focused on the meaning of the original autographs of the Old Testament, has recognized that the Septuagint has a significant contribution to make within this field of study. This position has been supported by Biblical scholars who have employed the Text Critical method in determining the authoritative text of the Old Testament. They employ the Text Critical method in their comparison of the Masoretic Text, the Samaritan Pentateuch, The Dead Sea Scrolls and most recently, the Septuagint to find traces of the original OT autographs.